Clinico-pathologic correlation in ocular sarcoidosis - Arthi Rao; Jodi Hwang; Joyce Wen; Sarah Edminster; Maria Sibug-Saber; Narsing Rao; Brian C. Toy (American Journal of Ophthalmology Case Reports)
Purpose: This case describes the unique course and management of a patient with progressive, refractory multi-system sarcoidosis that initially presented with ocular and dermatologic findings. Observations: A 47-year-old male presented with acute anterior uveitis and was found to have simultaneous inflammation of his skin at a tattoo site. Diagnosis of ocular sarcoidosis was confirmed through skin biopsy. Treatment with prednisone and adalimumab was initiated. Despite systemic immunosuppression and control of systemic inflammation, the patient had refractory ocular disease and developed bilateral disc edema and peripapillary choroidal neovascular membranes with subretinal fluid, so oral methotrexate and as-needed intravitreal bevacizumab injections were added. However, the patient manifested hepatic and worsening pulmonary involvement, prompting discontinuation of both methotrexate and adalimumab. Biopsy of the liver later confirmed hepatic sarcoidosis over drug-induced liver injury. Out of precaution for methotrexate-associated hepatic toxicity, mycophenolate mofetil was initiated instead, which then led to resolution of the subretinal fluid and disease quiescence. Conclusions and Importance: This case offers insight into the varying presentation and recalcitrant course of sarcoidosis. It documents a clinicopathologic case with unique initial presentation with biopsies of multiple organs, escalation of therapy with several immunomodulatory agents, and multidisciplinary collaboration to achieve ocular and systemic quiescence.